2020
DOI: 10.3390/brainsci10070455
|View full text |Cite
|
Sign up to set email alerts
|

Is Visual Creativity Embodied? Thinking Aloud While Performing the Creative Mental Synthesis Task

Abstract: Over time, the view that creativity is embodied has emerged. In order to explore if visual creativity is supported by embodied mechanisms, the simulation approach was used as a framework of reference. The idea that visual creativity relies on mental representations that implement motor processes was faced. Participants were instructed to think aloud while carrying out the Creative Mental Synthesis Task, which allows to form pre-inventive structures and interpret them according to a specific category. Two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The role of spatial manipulation in creative tasks is also consistent with those studies using the think-aloud method in order to reveal mental processes actively involved in creativity. For instance, Palmiero and Piccardi’s study [ 56 ] revealed that spatial thoughts—containing spatial information of size and rotation—generated during the preinventive phase positively predicted the originality of productions during the invention phase. Although we did not detect mental imagery directly, the assumptions reported above could represent a relevant point to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…The role of spatial manipulation in creative tasks is also consistent with those studies using the think-aloud method in order to reveal mental processes actively involved in creativity. For instance, Palmiero and Piccardi’s study [ 56 ] revealed that spatial thoughts—containing spatial information of size and rotation—generated during the preinventive phase positively predicted the originality of productions during the invention phase. Although we did not detect mental imagery directly, the assumptions reported above could represent a relevant point to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize and state that in a theory of mental synthesis—timing is key [ 39 , 40 , 41 ]. If the neuronal ensembles for the dolphin and the pineapple are simultaneously activated, the child could perceive the dolphin and the pineapple simultaneously.…”
Section: Neuroanatomical and Neurophysiological Relevancies And Irrel...mentioning
confidence: 99%
“…Palmiero et al [ 21 ] emphasized that visual creativity related to object originality can be embodied, to some extent, as perceptuo-motor codes, suggesting that simulations and other forms of knowledge representation permeate grounded cognition. Many studies in this Special Issue instead address embodiment in the context of the bodily awareness as the start for the sense of ownership (the sense that one’s body is one’s own) and the sense of agency .…”
mentioning
confidence: 99%